Test Signal Selection for Determining the Sound Scattering Coefficient in a Reverberation Chamber - KAMISIŃSKI, Tadeusz; BRAWATA, Krzysztof; PILCH, Adam; RUBACHA, Jarosław; ZASTAWNIK, Marcin (Archives of Acoustics, 2012)
The paper focuses on the problem of test signal selection in determining the sound scattering coefficientin accordance with ISO 17497-1. Research shows that the use of MLS signal is preferred in this procedure.The sine sweep signal, despite its advantages, presents certain limitations if the sample is moving duringmeasurement. An attempt has been made to develop a method that allows for minimization of error,demonstrating the dependence of the obtained values of the sound scattering coefficient on the rotationalspeed of the turntable and type of test signal. Conditions for the application of the sine sweep signals incontinuous and discrete measurements were defined.